COLLABORATIVE MODEL BETWEEN GOVERNMENT AND LAW ENFORCEMENT COMBATING ILLEGAL GOLD MINING IN NORTH SUMATRA - Siregar, Silvina Sari; Sundari, Cici; Dastina, Wenny (Universitas Padjadjaran, 2026)
This study aims to analyze in depth the collaborative governance model between local governments and law enforcement officials in controlling illegal gold mining in North Sumatra Province. The research uses a qualitative, descriptive-analytical approach based on secondary data from policy documents, regulations, and media reports. The analysis is carried out through a thematic approach, identifying patterns of interaction among actors, coordination mechanisms, the distribution of authority, and decision-making processes in collaborative practices. The analysis technique uses NVivo 12 Plus, a qualitative document analysis tool, on a computer. Their equipment is easy to use and can process words and explore word speed, attributes, and big data case scenarios. The results show that collaboration has occurred through a multi-actor approach, but it remains administrative and has not been systematically institutionalized. The main limitations lie in overlapping authority, weak coordination across sectors, and the absence of a sustainable, formal collaborative forum. In addition, the approach used remains predominantly repressive and has not addressed prevention grounded in community empowerment. This study concludes that the existing collaboration model has not reached the integrative collaborative stage. Therefore, it is necessary to strengthen institutional design, clarify the roles of actors, and establish a structured coordination mechanism to increase the effectiveness of illegal mining control.